Unusual energy separation of subbands in Si(111) p-channels induced by In adsorption - Ayob, Nur Idayu; Takeda, Sakura Nishino; Sakata, Tomohiro; Yoshikawa, Masaaki; Morita, Makoto; Daimon, Hiroshi (Japan Society of Applied Physics, 2015)
We investigated the dispersion structure of the hole subbands in vicinal Si(111)4 ' 1-In surfaces directly by angle-resolved photoelectron spectroscopy. In this study, three inversion layers with different impurity concentrations and numbers of times of flash annealing (FA) were investigated. We observed wider energy separations of subbands levels for the sample with a less number of FA and a higher impurity concentration. However, the observed energy levels and separations had smaller binding energy than those calculated by triangle potential approximation. We found that the discrepancies were due to the out-diffusion of Arsenic atoms from the sub-surface region of silicon via high temperature FA. The possible potential profile of the space charge layer after considering the out-diffusion of Arsenic dopant atoms at the subsurface region was proposed.